2013
DOI: 10.1186/1471-2180-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of mycoplasma-contaminated Orientia tsutsugamushi strains by repeating passages through cell cultures with antibiotics

Abstract: BackgroundMycoplasmas-contamination of Orientia tsutsugamushi, one of the obligated intracellular bacteria, is a very serious problem in in vitro studies using cell cultures because mycoplasmas have significant influence on the results of scientific studies. Only a recommended decontamination method is to passage the contaminated O. tsutsugamushi strains through mice to eliminate only mycoplasmas under influence of their immunity. However, this method sometimes does not work especially for low virulent strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…To obtain a Mycoplasma -free stock of strain WB-8-2 T for deposition and distribution, 50 μg ml −1 lincomycin was added to the medium and cell cultures were exposed to the antibiotic-supplemented medium for 6 weeks (Ogawa et al , 2013). Cultures were shown to be negative for infection with Mycoplasma species at 4, 5 and 6 weeks by using the PCR assay (data not shown), after which time the antibiotic was removed from the medium.…”
mentioning
confidence: 99%
“…To obtain a Mycoplasma -free stock of strain WB-8-2 T for deposition and distribution, 50 μg ml −1 lincomycin was added to the medium and cell cultures were exposed to the antibiotic-supplemented medium for 6 weeks (Ogawa et al , 2013). Cultures were shown to be negative for infection with Mycoplasma species at 4, 5 and 6 weeks by using the PCR assay (data not shown), after which time the antibiotic was removed from the medium.…”
mentioning
confidence: 99%
“…Mycoplasma organisms (except M. pneumoniae ) are susceptible to lincosamides, including clindamycin [2,15,27,28], whereas Rickettsia and Orientia are high-level resistant to clindamycin (MIC > 32 mg/L, Table 1). Studies have reported that lincosamides can decontaminate cell cultures from mycoplasmas [16,29]. However, lincosamides are bacteriostatic, and the MBC/MIC ratio was reportedly higher than 32 [30].…”
Section: Resultsmentioning
confidence: 99%
“…hominis and M . orale ) were tested in that study [16]. Fluoroquinolones and aminoglycosides have the potential for mycoplasma decontamination in Orientia culture due to the intrinsic resistance of Orientia to these classes of antibiotics [17].…”
Section: Introductionmentioning
confidence: 99%
“…The mycoplasma-free, highly virulent Ikeda strain of O. tsutsugamushi [9] was used in this study. For the inoculation, the Ikeda strain was deposited on monolayers of L-929 cells for 1 h. The inoculated cells were washed twice with Dulbecco's phosphate buffered saline (PBS, SigmaeAldrich Japan Co.…”
Section: Propagation Of O Tsutsugamushimentioning
confidence: 99%